PENYULUHAN HUKUM HAK TERSANGKA DAN TERDAKWA DALAM PROSES PEMERIKSAAN DI KEPOLISIAN, KEJAKSAAN, DAN PENGADILAN - Wachid Rowinanto; Andrew Kristianto Silalah; Erwin Owan Hermansyah Soetoto (Abdi Bhara, 2023)
Suspects and defendants need to know the rights theyhave in the criminal justice process in Indonesia. The aim is tofind out what legal remedies can be taken if it turns out that thereare deviations from the rights of suspects and defendants carriedout by law enforcement officials, both in the process at the police,prosecutors, and courts. The research used is a normativejuridical research that is normative, namely examining the lawwhich is conceptualized as a norm or rule that applies andbecomes a reference for the community. The rights of a suspector defendant must have been given during the examination,starting from the preliminary examination, prosecution andexamination before a court trial and in accordance with theCriminal Procedure Code. With the conclusion that the rights ofsuspects and defendants have been regulated in detail in theCriminal Procedure Code, namely in the following articles,namely articles 50 (paragraphs 1, 2 and 3), 51 (letters a and b),52, 53 (paragraphs 1 and 2), 54, 55, 56 (verses 1 and 2), 57(verses 1 and 2), 58, 59, 60, 61, 62 (verse 1), 63,64,65, 66, and68. Investigation , prosecute, and punish crimes or violationsintended to establish order, peace and security for the communityand must not injure and deprive individuals of their rights.Recognition of the rights of suspects in the national criminal lawsystem is regulated in the Criminal Procedure Code and LawNumber 48 of 2009 concerning Judicial Power which regulateslegal remedies that can be taken by suspects if it turns out thatthe suspect's rights are not enforcede.